Analisis Pendapatan Usaha Pengrajin Anyaman Rotan Masyarakat Kota Pagar Alam Provinsi Sumatera Selatan (Studi Kasus di Kelurahan Prahu Dipo Kecamatan Dempo Selatan) - Rahmadi, Selamet; Nurhayani, Nurhayani; Putri, Rayhan Amelia (Jurnal Paradigma Ekonomika, 2024)
One of the small and medium industries that are developing in Prahu Dipo Village is the rattan woven craft industry, which not only weaves rattan, craftsmen also market the woven products. This research aims to analyze: 1) Analysis of the socio-economic characteristics of rattan woven craftsmen in Prahu Dipo Village, South Dempo District, Pagar Alam City, South Sumatra Province; 2) The influence of business capital, working hours and digital marketing on the income of rattan woven craftsmen. The independent variabels used in this research are business capital, working hours and digital marketing, while the dependent variabel is income. This research uses multiple linear regression analysis. Based on the results of multiple linear regression, it can be concluded that jointly the independent variabels business capital, working hours and digital marketing have a significant effect on the income of rattan woven craftsmen. partially the variabels business capital and digital marketing have a significant effect on the income of craftsmen rattan weaving, while working hours do not have a significant effect on the income of rattan woven craftsmen.